Chitosan: A Versatile Bio Polysaccharide with Potential Applications in the Food Industry - , Kanneboina Soujanya, Meduri Swapna Sree, Butti Prabhakar, T. Supraja, P. Yasaswini (Archives of Current Research International, 2024)
Chitin is the first identified, renewable and 2nd most prevalent polysaccharide after the cellulose on the earth. It serves as a primary component of fungi cell walls, exoskeletons of arthropods, insects, molluscs, scales of fish and cephalopod beaks. Chitosan is linear deacetylated polysaccharide form of chitin, composed of glucosamine and N-acetyl glucosamine residues linked by β-1,4 bonds. Network of molecules involved rather than just one polymer, which differ in their size, composition, monomer distribution and these properties influence the physicochemical, technical and biological performance of the polymer. Since 1970, chitosan has attracted various scientific and industrial attention because of its unique macromolecular structure, biodegradability, biocompatibility and its potential intrinsic functional characteristics such as antiviral, active element of the diet for weight loss, anticancer, antifungal activity, antimicrobial properties. Chitosan and its derivatives have a wider spectrum of applications in medicine, pharmacy, agriculture, textiles and food industries. Within the health sector, chitin and its derivatives are employed as functional fibers since they possess prebiotic properties, lower blood LDL cholesterol, improve (ameliorate, enhance) glucose intolerance, boost insulin production, alleviate dyslipidemia, and safeguard gut integrity. These unique and excellent structural properties (qualities, attributes) of chitosan and its derivatives permits chitosan for unlimited food applications.